Yield Performance of Short-Stem Promising Mutant Lines of Mentik Wangi Rice Induced by 200 Gy Gamma Irradiation - Fitria Roviqowati; Desfinenda Calistarajni; Parjanto Parjanto; Edi Purwanto; Ahmad Yunus (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2024)
The demand for rice in Indonesia continues to increase but production has decreased. Efforts that can be made are the use of local varieties of mentik wangi rice. Mentik wangi rice has the disadvantages of long life, high stems, and low crop production. As a solution, plant breeding is carried out in the form of mutation by giving gamma irradiation which can improve unwanted genetic traits and produce superior varieties with the dose used of 200 gray. This study aims to evaluate the yield potential of promising mutant strains with 200 gray gamma irradiation on mentik wangi rice and get mutant strains that have superior criteria for short-stemmed, short-lived, and high-yielding. This research was conducted in the rice field of Ngampel Hamlet, Gentungan Village, Mojogedang, Karanganyar, Central Java. The research was conducted in June-October 2023. The design used was a Randomized Complete Group Design (RCBD) with a single factor, namely strains consisting of 14 mutant strains and 1 control strain with 3 repetitions. The results of observations were analyzed by Analysis of Variance (ANOVA) at the 5% level and continued with Duncan Multiple Range Test (DMRT) at the 5% level. All tested strains produced the expected superior criteria, namely short stem, short age, and high productivity.